Inventory of Pests and Parasites in the Cultivation of Hotate Shellfish (Patinopecten yessoensis) in Funka Bay, Hokkaido, Japan - Kezia Belva Putri Merdeka; Anandita Ekasanti; Dewi Nugrayani; Daisan Matsui Gyogyobu (PT. Artha GenetikaLab Indonesia, 2024)
Hotate Shellfish Cultivation is the largest shellfish cultivation in the world, but many pests and parasites are found. This research aims to inventory the types of pests and parasites found in the cultivation of Hotate Shellfish (Patinopecten yessoensis) in Funka Bay, Hokkaido, Japan. The objects used for this research were 54 Hotate shellfish, consisting of three life stages of shellfish, namely seed shellfish, juvenile shellfish, and adult shellfish. This research was carried out using observation and random sampling methods to determine the types and percentages of pests and parasites present during the research. This research was carried out for seven months from 13 April to 6 December 2022 at the Daisan Matsui Company, Ohama, Oshamambe, Hokkaido, Japan. The results of this research show that there are four types of pests, namely Starfish, Purple Shellfish, Crustaceans, and Sea Pineapples as well as two types of parasites, namely Annelid Worms and Barnacles which attack shellfish cultivation. The percentage of shellfish at three life stages that were attacked by parasites was 75.93%. There are several factors that control the attachment of pests and parasites, including substrate availability, nutrient availability, and environmental considerations. The surfaces and nutrients provided by hotate culture facilities provide adequate conditions for pest settlement and growth.